Dynamic relationship between macroeconomic variables and finance sector market indices / Mohd Shafiq Bohari and Shahiza Mohammad - Bohari, Mohd Shafiq; Mohammad, Shahiza (Faculty of Business and Management, 2013)
The aim of this study is to investigate the relationship between Exchange Rate, Inflation Rate, Money Supply, and Interest Rate to the Finance Sector Market Indices. The study used Simple Linear Regression and Multiple Linear Regression in order to find the relationship among those indices. The monthly closing data were collected from January 2005 until December 2012. From the result, it reveals that certain variables have a significant negative relationship towards Finance Sector Market Indices and the others are insignificant. It means that there are macroeconomic variables that interdependence towards the Finance Sector Market Indices. Based on the results, it shows further understanding of the relationship between the macroeconomic variables to the Finance Sector Market Indices and it may be useful for regulators, investors, and speculators.